Chapter L’impatto del Service-Learning su docenti e educatori - Kulberg Taub, Mikol (Firenze University Press, 2023)
The poster describes the first phase of a research on the impact of Service-Learning on in-service and future teachers and educators, as mentioned in the research questions. This study started with a literacy review about Service-Learning, in both national and international framework. The Italian way of Service-Learning has been further investigated, using the work of Don Milani as a cultural reference. The research continued with an analysis of the normative and national literature about this approach. It is followed by a systematic review concerning the research questions, making use of Prisma statement. Four different databases were used for the investigation. As result of using a list of inclusion/exclusion criteria, 60 studies were eligible for full text analysis. The results underlined a lack of studies focusing on the Italian context, and a strong unbalance between studies concerning in-service teachers and pre-teachers. Results will orient the empiric part of the research for future steps.